Establecimientos turísticos y consumo de la producción local del cantón Riobamba, provincia de Chimborazo. - Ortega Conde, Daisy Jeraldy (2024)
ABSTRACT: This research aimed to analyze the relationship between tourist establishments and the consumption of local artisanal products in the Riobamba Canton, Chimborazo Province. The main issue addressed is the deficient consumption of local artisanal products. The research type encompassed documentary, field-based, descriptive, correlational, quantitative, and qualitative methodologies. For surveys, the population was determined according to each variable. Regarding the independent variable, the decision was made to work with personnel employed within various types of tourist establishments including accommodation, food, and beverage services in the Riobamba Canton. Meanwhile, for the dependent variable, local artisanal producers were chosen. Data analysis was conducted using the SPSS program with Spearman's Rho correlation statistic. Finally, conclusions and recommendations were drawn to develop a tourist guide aimed at promoting the value of local artisanal products in the city of Riobamba. The objective is to educate tourists about the significance of each artisanal piece, particularly emphasizing the cultural value inherent in each creation.